Solid state devices, 1976 : seven invited papers presented at the Sixth European Solid State Device Research Conference (ESSDERC) held at Technische Universitat, Munchen, 13-16 September 1976 - European Solid State Device Research Conference (ESSDERC) 1976 : Technische Universitat, Munchen); Muller, R. (Ralph), 1933-; Lange, E. (Bristol : The Institute of Physics, 1971)
Contains invited papers presented at the European Solid State Device Research Conference.
Keywords: Semiconductors -- Congresses